A Mathematical Modeling of the Vaccination Effect on the SARS-CoV-2 Transmission: Analysis and Simulation - Saadi, Rami Raad; Al-Husseiny, Hassan F. (Iraqi Journal of Science, 2024)
Several illustrative studies on the mathematical modeling and analysis of the Coronavirus have been carried out in a short period of time. There is not enough work that accounts for the vaccination campaign's two stages. In this work, a mathematical model is created to show the impact of the recent two-stage vaccination treatment on the Coronavirus. In the proposed model, five compartments are constructed, namely the susceptible individuals , the first dose of vaccination  , the second dose of vaccination , infected  and recovered population . The uniqueness, boundedness and existence of the solutions of this model have been discussed. All potential model equilibrium points are determined. The local as well as global stability of the system in terms of the basic reproduction number is investigated. Numerical simulation is also carried out to investigate the influence of parameters affecting the dynamics of the model and to support the gathered analytical findings of the model.